Biodiversity of Aspergillus section Nigri populations in Argentinian vineyards and ochratoxin A contamination - Chiotta, María Laura (2013)
Aspergillus section Nigri are described as the main source of ochratoxin A(OTA) contamination in grapes and wine worldwide. The knowledge of the factors affecting grape contamination by species included in this section and OTA production is essential to be able to reduce their presence, not only to improve wine quality, but also to maintain their safety. Therefore, the aims of this study were to determine the incidence of Aspergillus section Nigri species harvested in different grape-growing regions from Argentina, their ability to produce OTA, to correlate with meteorological conditions and geographical coordinates with their prevalence and to evaluate the OTA natural occurrence in grapes and wines. The morphological identification showed that A. niger aggregate species were the most prevalent ones, followed by A. carbonarius and Aspergillus uniseriate. These populations were confirmed through using AFLP markers and sequencing and, A. tubingensis was separated from A. niger aggregate. Climatic factors, altitude, longitude and latitude have influenced on the distribution of species included in the section. A. carbonarius and A. niger were OTA producers but differed in their OTA producing ability. Temperature was the factor which influenced the most over the highest incidence of A. carbonarius in La Rioja and San Juan regions. The trellis system in vineyards and drip irrigation also influenced the species isolation. The OTA levels detected in grapes and wines were low, but grape variety was more important in susceptibility to fungal infection and OTA levels.